An Evaluation and Modification of World Conservation Union Red List Criteria for Classification of Extinction Risk in Vascular Plants - David A. Keith (Conservation Biology, 1998)
The World Conservation Union (IUCN) Red List criteria endorsed in 1994 consist of a set of decision rules based on quantitative thresholds of population size, distributional range, rates of decline, and extinction risk. I evaluated these criteria using data on 68 vascular plant taxa from southeastern Australia and found that deficiencies could be overcome with modifications that did not substantially alter the structure of the IUCN rule set. These modifications included smaller distributional thresholds appropriate to sessile organisms, inclusion of life‐history and land‐based attributes, an amendment to account for skewed metapopulation structure, and inclusion of a rule addressing number of populations and qualitatively defined classes of threatening processes. I reviewed the strengths and weaknesses of decision rules for risk classification such as those endorsed by the World Conservation Union compared with intuitively based qualitative schemes in traditional use. I concluded that explicit schemes foster greater accuracy and precision in risk classification, are more defensible in the face of challenges, and define an agenda for data collection that is essential for the ongoing assessment and management of threatened species. Evaluación y Modificación de los Criterios de Clasifícación de Riesgo de Extinción en Plantas Vasculares de la Lista Roja del IUCN Los criterios de la lista roja del IUCN establecidos en 1994 constituyen un juego de reglas de decisión basadas en límites cuantitativos de tamaño poblacional, rango de distribución, tasas de declive y riesgo de extinción. Evaluamos estos criterios usando datos de 68 taxa de plantas vasculares del sureste de Australia y encontramos que ciertas deficiencias pueden ser resueltas con modificaciones que no alteran sustancialmente la estructura del juego de reglas del IUCN. Estas modificaciones incluyen límites de distribución más pequeños apropiados para organismos sésiles, inclusión de atributos de la historia de vida y en base al terreno, una enmienda que considere estructucturas metapoblacionales sesgadas y la inclusión de una regla que considere el número de poblaciones y clases cuantitativamente definidas de los procesos de amenaza. Revisamos la fortaleza y debilidad de las reglas de decisión para clasificación de riesgos como lo son las reglas del IUCN comparadas con esquemas cualitativos con bases intuitivas de uso tradicional. Concluimos que los esquemas explícitos amplían la precisión y exactitud de las clasifcaciones de riesgo, son más defensivas en presencia de desafios y definen una agenda para la colección de datos que es esencial para la evaluación en curso y manejo de especies amenazadas.